Legal Regulation of Legal Relations in the Field of Robotics and the Application of Artificial Intelligence Technologies - Olga V. Kudryavtseva (LAW AND BUSINESS, 2026)
The article analyzes the legal regulation of relations in the field of robotics and artificial intelligence in Russia for 2026. The development of federal laws, a special tax regime, mechanisms of administrative responsibility, experimental legal regimes, as well as a discussion about the legal personality of “non-biological members of society” are being investigated. Conclusions are formulated on the formation of a Russian model of regulation based on technological sovereignty, the priority of human rights and the inadmissibility of endowing technologies with legal personality.